2011
DOI: 10.1103/physrevb.83.224303
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Raman study of isostructural YCrO3and YMnO3: Effects of structural distortions and twinning

Abstract: Polarized Raman spectra of isostructural orthorhombic YCrO 3 and YMnO 3 single crystals were collected at same conditions using different laser excitation in the visible range. The symmetry of the observed lines was determined and they were assigned to definite atomic vibrations based on lattice dynamical calculations. The frequencies of the lines of the same origin in both compounds are close, however, their intensities differ significantly. While the different intensity of the modes, activated by the Jahn-Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 35 publications
6
40
0
Order By: Relevance
“…In order to study these features in such materials, it is essential to study the lattice dynamics. [17][18][19][20][21][22] The phonon behavior of these multiferroic materials shows an anomaly near Nèel transition temperature in Raman modes. There are several reports which deal with the Raman studies of multiferroic-materials.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study these features in such materials, it is essential to study the lattice dynamics. [17][18][19][20][21][22] The phonon behavior of these multiferroic materials shows an anomaly near Nèel transition temperature in Raman modes. There are several reports which deal with the Raman studies of multiferroic-materials.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies were interested in the coupling between phonon modes and the magnetic ordering, which was done without a complete Raman mode assignment. At the beginning of this decade, N. Iliev et al and N. D. Todorov et al have investigated Raman modes of LaCrO 3 and YCrO 3 single crystals, respectively . These different studies were conducted on single crystals with micrometric size, which make impossible any crystallographic orientation and then phonon modes assignments become a nontrivial task.…”
Section: Introductionmentioning
confidence: 99%
“…Out of these 60 modes, 24 modes (7 A 1g + 5 B 1g + 7 B 2g + 5 B 3g ) are Raman active . In the present study, we have observed 17 Raman active modes among 24 allowed one in the spectral range of 130–800 cm −1 at 300 K, which matches fairly well with the previous studies on YCO . The higher Raman peaks are assigned to the vibration of oxygen atoms (O1 and O2) only whereas the lower Raman peaks are attributed to the vibration of both Y and O atoms .…”
Section: Resultsmentioning
confidence: 99%